Analysis of the Relationship Between Nutritious Breakfast Consumption and Learning Concentration of Early Childhood - Khuliyatul Nusroh; Izza Ikromatus Sa’adah; Novida Riasti; Aisya Mashadi; Rachma Hasibuan (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2026)
Acceptance of nutritious food among young children is a key element in supporting optimal growth and development. This study aims to investigate childrenâ€™s food preferences and the impact of environmental factors on healthy eating habits using a literature review method. Data were collected by analyzing scientific articles published between 2020 and 2025 from various credible sources, using keywords such as â€œearly childhood food preferencesâ€ and â€œenvironmental influences on childrenâ€™s eating habits.â€ The analysis reveals that childrenâ€™s food preferences are influenced by various biological factors, such as genetics and sensory development, as well as environmental factors, including parenting practices, media exposure, and the role of educational institutions. Parents who implement healthy eating patterns and provide positive role modeling play a crucial role in shaping childrenâ€™s eating habits. Meanwhile, early childhood education institutions contribute through engaging and enjoyable nutrition education programs. However, picky eating behavior remains a challenge in establishing healthy dietary patterns. Therefore, a comprehensive approach involving families, schools, and the broader community is necessary to build healthy eating habits from an early age. These findings are expected to serve as a foundation for developing effective and sustainable nutrition interventions for young children.